A vizuális narráció eszköztára a Design-könyvek sorozatában - Révész, Emese (Studia Litteraria, 2019)
The study focuses on one of the outstanding Hungarian examples of wordless picturebook (silent book), the so called Design book series from Csimota Kiadó publishing house, which has produced 23 volumes since 2006. In the series five different graphical designer recreates a classic tale in a separate volume each, without any text, only with pictures. In the small sized (12x12 cm), hard cover volumes 20 pages were dedicated for retelling a world famous fable. The first series in 2006 introduced the story of Little Red riding Hood, The Three Little Pigs followed in 2007, then Snow White and the Seven Dwarfs (2009), Puss in Boots (2012) and the most recent one is Sleeping Beauty (2015-2016) with only three volumes so far. The study examines the expression of the stories by analysing the narrative tools (picture-text relationship, colours, visual metaphors, intermediality etc.).